2012
DOI: 10.1039/c2ra20554h
|View full text |Cite
|
Sign up to set email alerts
|

Collapse and Stability of functionalized Carbon Nanotubes on Fe (1 0 0) Surface

Abstract: The collapse and stability of carbon nanotubes (CNTs) functionalized by corrosion inhibitor molecules on the Fe (1 0 0) surface were studied using molecular mechanics and molecular dynamics simulations. The results show that the pristine CNTs can approach and even collapse spontaneously onto the Fe surface due to the van der Waals force between them when the CNT diameter exceeds a certain threshold. To avoid collapse of the CNTs, they are randomly sidefunctionalized by three corrosion inhibitors. When the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…[37][38][39][40] Moreover, it has been successfully used to study the mechanical properties and radial collapses of CNTs under hydrostatic pressure. [27][28][29][30][31][32]41,42] In the present paper, periodic boundary conditions are used in all systems, including intrinsic SWCNTs (10, 10) and (17, 0) and SWCNTs with divacancy and 5-8-5 defects with the same diameter and length of 25 Å. First, MM simulations are performed to find the thermal stable morphology and achieve a conformation with minimum potential energy for all SWCNTs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40] Moreover, it has been successfully used to study the mechanical properties and radial collapses of CNTs under hydrostatic pressure. [27][28][29][30][31][32]41,42] In the present paper, periodic boundary conditions are used in all systems, including intrinsic SWCNTs (10, 10) and (17, 0) and SWCNTs with divacancy and 5-8-5 defects with the same diameter and length of 25 Å. First, MM simulations are performed to find the thermal stable morphology and achieve a conformation with minimum potential energy for all SWCNTs.…”
Section: Methodsmentioning
confidence: 99%
“…After SWC-NTs collapse, the opposite walls of SWCNTs have almost entered into the strong-adhesive-binding region of the chemical bonds and the attractive vdW force exists between the opposite walls of the collapsed SWCNTs. [27,28,[30][31][32] The attractive vdW force between the opposite walls makes the total vdW energy of SWCNTs decrease. For SWCNT (10,10), the vdW energy variation is less than that of the internal energy, which shows that upon unloading the attractive vdW force is not large enough to stabilize the collapse state of SWCNT, and therefore SWCNT (10,10) can return to the origin state.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion current densities increased, due to the alloy having undergone corrosion. [35][36][37][38] Corrosion potential decreased, due to cathodic hydrogen evolution, and indicating that anodic alloy dissolution increased. The 4,5-DPM-functionalized CNT carbon-coated nickel alloy corrosion current densities decreased and corrosion potential increased due to strong physisorption of the 4,5-DPMfunctionalized CNT on the alloy surface.…”
Section: Electrochemical Stabilitymentioning
confidence: 99%
“…In addition to the axial buckling behaviors, the radial mechanical properties of CNTs are also significant. At present, the radial deformation of CNTs and CNTs filled with fullerene has been investigated comprehensively [26][27][28][29][30][31]. It is demonstrated that CNT filled with fullerenes presents an inhomogenous filling at the molecular scale, which should introduce strain inhomogeneity and lead to structural changes at lower pressures.…”
Section: Introductionmentioning
confidence: 99%